Optimize 2-D Path Planning of Mobile Robot by using ACO with Guidance Factor - Li Wang (Sir Syed University Research Journal of Engineering and Technology)
In this research article, the path planning of a mobile robot done by using ant colony optimization (ACO) with guidance factor. A two-dimensional (2-D) threat map structure design for path planning strategy, in which threat points are fixed in the path of moving robot. The two main objective of this research; to reach the mobile robot at the target position by using optimal route using ACO strategy. Secondly, by using guidance factor all the ants of ACO arrive at the fixed targeted area. Moreover, the results of the proposed algorithm compares with the classical ant system methodology. The simulated results show that the design method has short path planning and less steady state error to reach the designated path robustly.